Novel Handbell-Like ZnO Architectures Fabricated by One-Pot Sonochemical Method - Hu, H.M.; Deng, C.H.; Ge, X.Q.; Sun, M.; Zhang, K.H.; Yang, M.D. (Asian Journal of Chemistry, 2012)
A facile green ultrasonic-assisted chemical reaction has been employed to controllably fabricate handbell-like ZnO architectures without using any templates, surfactants and organic additives. The products were characterized by X-ray diffraction, energy dispersive X-ray spectrometry and field-emission scanning electron microscopy. Field-emission scanning electron microscopy observation indictates that most of the ZnO handbell-like structures are built by hexagonal trumpet-shaped shell (called as bell hood) and hexagonal rod-shaped core (called as bell tongue), which have the nature of hexagonal symmetry. The growth mechanism and its succedent evolution of handbell-like ZnO architectures contolled by dynamical process with the change of ultrasonic irradiating time are investigated.